2022
DOI: 10.3390/ijms23115929
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Protects the Intestinal Barrier by Activating Goblet Cell Maturation and Epithelial Proliferation in Radiation-Induced Enteropathy

Abstract: Radiotherapy or accidental exposure to high-dose radiation can cause severe damage to healthy organs. The gastrointestinal (GI) tract is a radiation-sensitive organ of the body. The intestinal barrier is the first line of defense in the GI tract, and consists of mucus secreted by goblet cells and a monolayer of epithelium. Intestinal stem cells (ISCs) help in barrier maintenance and intestinal function after injury by regulating efficient regeneration of the epithelium. The Wnt/β-catenin pathway plays a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Impaired intestinal stem cells by radiation retard epithelial cell proliferation and regeneration of the intestine [ 34 , 35 ]. In our previous study, we found that MF treatment promoted stem cell properties and increased epithelial proliferation [ 21 ]. Therefore, we assessed the epithelial proliferation capacity and intestinal stem cell ability in the combined PS and MF treatment under radiation exposure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Impaired intestinal stem cells by radiation retard epithelial cell proliferation and regeneration of the intestine [ 34 , 35 ]. In our previous study, we found that MF treatment promoted stem cell properties and increased epithelial proliferation [ 21 ]. Therefore, we assessed the epithelial proliferation capacity and intestinal stem cell ability in the combined PS and MF treatment under radiation exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The protective effects of MF on radiation-induced GI damage have been previously reported [ 17 , 19 , 20 ]. We also identified the stem cell preservative effects of MF in a radiation-induced intestinal injury mouse model [ 21 ]. However, a single therapy with PS or MF did not show survival effects in lethal dose irradiation in our data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the bottom of crypts, intestinal stem cells (ISCs) differentiate into goblet cells and promote epithelial regeneration against radiation-induced intestinal injury ( 46 ). It has been reported that the mucus secreted from goblet cells performs an important role in radiation-induced intestinal injury ( 47 ). While at the top of crypts, the most important intercellular tight junction is mainly composed of claudin and ZO-1, which exert a vital role in sustaining cell polarity and the intestinal epithelial barrier ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%